Comparing Bolt Implementation Methods in Vibration Testing for Accurate Dynamic Behavior Analysis - Jong Hyuk Back; Jeong Bin Bae; Ji Hye Kang; Jung Jin Kim (Applied Sciences)
Vibration testing is crucial for understanding structural dynamics, yet conventional modeling of bolt connections often leads to significant inaccuracies. This study systematically compares six bolt connection methods—bonded, adaptive bonded, joint, beam, screw, and fixed bolt—using a finite element analysis of a headlamp vibration test jig. The six bolt connection methods were selected based on approaches adopted in previous studies. The experimental results identified the joint connection method as the most accurate, minimizing deviations in natural frequency to 7.6 Hz compared to experimental tests at 493.2 Hz, while bonded methods overestimated the frequency at 544.1 Hz due to excessive stiffness assumptions. Efficiency analyses highlighted bonded methods as the most computationally streamlined, offering preprocessing times as short as 30 s and shorter overall analysis times. These findings emphasize the importance of selecting appropriate bolt connection methods in the early design phase to ensure accurate natural frequency predictions and mode shape representations. Although this study does not consider bolt preload forces, the work shows the possibility of offering practical guidelines for improving the reliability and efficiency of vibration test jig designs by bridging the gap between analysis and experimental results.